Fiscal implications of the ECB's public sector purchase programme (PSPP) - Harmen Lehment (Kiel Institute for the World Economy (IfW), 2018)
The large Public Sector Purchase Programme (PSPP) which the ECB started in 2015 on the basis of monetary policy purposes, had major side-effects on fiscal policy. One concerns the programme's uncommon seigniorage effects. We find that the PSPP not only led to partly negative seigniorage gains, but also produced super-seigniorage gains resulting from negative interest rates on the excess reserves which have been created by the programme. Another effect of the PSPP is its interference with fiscal debt management, thereby making fiscal budgets more vulnerable to changes in short-term interest rates. We also find that the experience with the PSPP suggests that fiscal policy should prepare for a greater role in fighting future recessions.
Keywords: E5; E6; H6; 330; central bank asset purchases; seigniorage gains; debt management; monetary-fiscal cooperation